The importance of nursing case report competition in clinical nursing (护理个案比赛在临床护理工作中的重要性) - LI Suqian (李苏茜); TANG Ling (唐玲); LI Ye (李野) (中西医结合护理)
Case report is a common type of academic paper, and nursing case report refers to the case report, nursing management and experience of one specific patient or a series of diseases. Carrying out the nursing case report competition is effective to improve the connotation of nursing specialty and quality of nursing. This paper reviewed studies on nursing case report in perspectives of its concept, origin, Traditional Chinese Medicine nursing case report, nursing case report competition, and briefly analyzed the importance of nursing case report competition in clinical nursing. (个案报告是一种常见的学术论文文体, 护理个案是护士对临床工作中具有特殊性或典型代表的一例或一类疾病的病例报告、护理经验和体会。开展护理个案比赛能够通过以赛促学的方式促进和提升临床护理专科内涵, 提高护理服务质量。本文将从个案报告的概念、起源、中医个案报告、护理个案报告、护理个案比赛等方面进行综述, 浅析护理个案报告对临床护理工作的指导意义。)